2014
DOI: 10.1002/ange.201407920
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Heme Dioxygenase Catalyzes Atypical Oxidations of 6,7‐Bicyclic Systems To Form the 6,6‐Quinolone Core of Viridicatin‐Type Fungal Alkaloids

Abstract: The 6,6-quinolone scaffold of the viridicatin-type of fungal alkaloids are found in various quinolone alkaloids which often exhibit useful biological activities. Thus, it is of interest to identify viridicatin-forming enzymes and understand how such alkaloids are biosynthesized. Here an Aspergillal gene cluster responsible for the biosynthesis of 4'-methoxyviridicatin was identified. Detailed in vitro studies led to the discovery of the dioxygenase AsqJ which performs two distinct oxidations: first desaturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The dioxygenase AsqJ (ANID_09227) from A . nidulans has previously been shown to introduce a double bond in the same position of a phenylalanine moiety of an intermediate in the cyclopenin/4’-methoxycyclopenin biosynthetic pathway [ 26 ]. However, deletion of asqJ did not result in any changes of the final product of CcsA and CcsC.…”
Section: Resultsmentioning
confidence: 99%
“…The dioxygenase AsqJ (ANID_09227) from A . nidulans has previously been shown to introduce a double bond in the same position of a phenylalanine moiety of an intermediate in the cyclopenin/4’-methoxycyclopenin biosynthetic pathway [ 26 ]. However, deletion of asqJ did not result in any changes of the final product of CcsA and CcsC.…”
Section: Resultsmentioning
confidence: 99%
“…1) and related compounds are produced by species in cladistically different sections of Aspergillus. It is produced by Aspergillus sclerotiorum in section Circumdati (Visagie et al a, b, c), Aspergillus jensenii in section Versicolores (reported as Aspergillus nidulans by Ishikawa et al 2014) and by A. fumigatus in section Fumigati (Frisvad and Dyer, unpublished). Penicillins (Fig.…”
Section: Unique Extrolites In Subgenus Fumigatimentioning
confidence: 95%
“…4 In the reactions of Fe/2OG monooxygenases from plants, fungi, and bacteria, different fates of the Fe(III)-OH/R• state (alternatives to step 4) lead to halogenation, desaturation, cyclization, ring-expansion and stereoinversion of aliphatic carbons. [14][15][16][17][18] With respect to biocatalysis and pharmaceutical synthesis, the abilities of certain Fe/2OG monooxygenases to install a halogen leaving group 14, [19][20] for chemoselective fragment couplings or an epoxide electrophile [21][22][23] for covalent capture of biomolecular targets are among the most potentially valuable. The mechanism of the latter reaction type is less thoroughly understood than those of either hydroxylation or halogenation, providing motivation for this study.…”
Section: Introductionmentioning
confidence: 99%